Examination of the Relationship Between Early Maladaptive Schemas, Attachment Styles and Adult Separation Anxiety ın a non-Clinical Sample - Cansu Selin Yurtseven, Ebru Özkul, (Pakistan Journal of Medical & Health Sciences, 2022)
Early maladaptive schemas are based on belief mechanisms that are shaped in the childhood of individuals and manifest in relationships in their future lives. These schemas consist of 5 domains and 18 sub-dimensions also affect the way people perceive others.Another factor that predicts relationships in adulthood is the quality of the attachment established with the caregiver in early life.Attachment types seen in adults are examined under 4 main headings. The aim of this study is to determine the level and existence of the correlation between early maladaptive schemas and attachment styles of individuals and their perceived separation anxiety in adulthood, using the correlational survey model. The scales used were, Personal Information Form, Young Schema Questionnaire ,Adult Attachment Scale, and Adult Separation Anxiety Questionnaire. 285 individuals, 148 women and 137 men, over the age of 18 and residing in Istanbul, participated in the study. According to the findings of the study, there is a positive correlation between the Fearful, Preoccupied and Dismissive Attachment subscale scores and the Adult Separation Anxiety Scale scores, and there is a negative significant relationship with the Secure Attachment subscale overall score. It is seen that the sub-dimensions of the Young Schema Questionnaire significantly predict separation anxiety in adults. On the other hand, it was found that the Young Schema Scale sub-dimensions were positively correlated with the scores of other attachment styles, except for secure attachment. The obtained results support previous studies.